Chiral Polyoxygenated Tertiary Alcohols through Kiyooka Aldol Reaction - Lücke, Daniel; Kalesse, Markus (Synlett, 2022)
Here we present our work on a Kiyooka aldol protocol for the stereoselective synthesis of tertiary alcohols. In the obtained products, three oxygenated carbon atoms that could further be differentiated flank the chiral tertiary alcohol. This methodology can be applied to simple aromatic or aliphatic aldehydes and more complex substrates bearing a chiral center in the α- and/or β-position. For complex substrates, an unexpected dependency between stereoselectivity and double-bond geometry of the ketene acetal was observed. Furthermore, applications in or towards the synthesis of natural products are presented.1 Introduction2 Scope of the Reaction3 Synthetic Applications4 Conclusion
Keywords: aldol reaction; tertiary alcohols; ketene acetal; stereoselective synthesis; double-bond geometry